Exon Shuffling and Origin of Scorpion Venom Biodiversity - Wang, Xueli (Toxins (Basel), 2016)
Scorpion venom is a complex combinatorial library of peptides and proteins with multiple biological functions. A combination of transcriptomic and proteomic techniques has revealed its enormous molecular diversity, as identified by the presence of a large number of ion channel-targeted neurotoxins with different folds, membrane-active antimicrobial peptides, proteases, and protease inhibitors. Although the biodiversity of scorpion venom has long been known, how it arises remains unsolved. In this work, we analyzed the exon-intron structures of an array of scorpion venom protein-encoding genes and unexpectedly found that nearly all of these genes possess a phase-1 intron (one intron located between the first and second nucleotides of a codon) near the cleavage site of a signal sequence despite their mature peptides remarkably differ. This observation matches a theory of exon shuffling in the origin of new genes and suggests that recruitment of different folds into scorpion venom might be achieved via shuffling between body protein-coding genes and ancestral venom gland-specific genes that presumably contributed tissue-specific regulatory elements and secretory signal sequences.